Trajectories and risk factors of persistent cough after pulmonary resection: A prospective two‐center study - Xuefeng Sun; Zihua Lan; Shaopeng Li; Shujie Huang; Cheng Zeng; Junhan Wu; Qibin Chen; Yizhang Chen; Ziguo Chen; Yong Tang; Guibin Qiao (Thoracic Cancer, 2023)
Abstract Background Persistent cough is one of the most frequent complications following lung cancer surgery. To promote optimal recovery, we conducted a study to investigate the trajectories of coughing symptoms and their impact on quality of life (QOL), as well as to identify potential risk factors of persistent cough after pulmonary resection (CAP). Methods This prospective observational study assessed patients who underwent pulmonary resection for lung tumor at two medical centers in China. Persistent CAP was evaluated before surgery, at discharge, and 1, 3, and 6 months following surgery using visual analog scale (VAS), cough symptom score (CSS), and Leicester Cough Questionnaire in Mandarin Chinese (LCQ‐MC). Univariate and multivariate logistic regression analyses were conducted to explore independent risk factors for persistent CAP. Results Of the 506 enrolled patients, 130 patients were diagnosed with persistent CAP with an incidence of 25.69%. Compared to the noncough group, patients with persistent CAP reported significantly higher VAS (p < 0.001) and CSS scores (p < 0.001) and experienced worse QOL (p < 0.001) for up to 6 months, particularly at 1 month following surgery. Multivariable regression analysis revealed that a duration of anesthesia exceeding 156 min (odds ratio [OR]: 1.847, 95% confidence interval [CI]: 1.156–2.951, p = 0.010) and gastroesophageal acid reflux (GER) (OR: 3.870, 95% CI: 2.376–6.304, p < 0.001) were independent risk factors of persistent CAP. Conclusion Patients who suffer from persistent CAP face a substantial burden and diminished QOL for an extended period compared to noncough patients. Moreover, prolonged duration of anesthesia and postoperative GER are potential risk factors of persistent CAP.